The finite element study of femoral-tibial stress - Kuo, Tzu Jye (2015)
This project examined the stress distribution on the femur and tibia portion of the knee joint using finite element analysis. As compared to previous final year projects, where only the tibia bone was studied, this project focused on the fully intact knee joint to give a more comprehensive analysis of the stress distribution. From the results obtained, the stress pattern is comparable to previous studies and final year projects of the intact knee, with slight variations pertaining to certain stress values. This may be due to slight differences in material properties as well as the assigned load and fixed boundary conditions. Further work may involve the same cadaver used, with the instalment of knee implants such as the implants used in the Unicompartmental Knee Arthroplasty (UKA) procedures, to have a better understanding and analysis of reasons for failure.